(untitled) (Slavic Studies, 2024)
For a few decades, the proponents of feminine forms of names of professions, functions, academic titles and degrees have grown in numbers, but their adversaries still usually have the upper hand. The latter believe that feminine forms such as profesorka, rektorka, dziekanka, doktorka, dyrektorka, ministerka are less prestigious, because they are not common in everyday speech and sound strange, even ridiculous. The article presents data from 54 obituaries of deceased women, as follows: 1. obituaries with generic forms identical to masculine forms that double as feminine (20, or 37.3% of selected obituaries); 2. obituaries with solely feminine forms (2, or 3,7%); 3. obituaries with an equal number of feminine forms and generic forms identical to masculine forms that double as feminine (4, or 7,4%); 4. obituaries with more feminine forms than generic forms identical to masculine forms, that double as feminine (7, or 12,8%); 5. obituaries with more generic forms identical to masculine forms that double as feminine than feminine forms (21, or 38,8%). The obituaries are largely dominated by generic forms identical to masculine forms that double as feminine. This fact is symptomatic of conservatism in language, which has been for the most part successfully stamped out by the Czechs and Germans, nations that favour practical solutions and pursue a democratic language policy.